P-397 How do extracellular vesicles secreted by human embryos impact decidualized endometrial stromal cells?. (30th June 2022) - Pavone, V; Makieva, S; Giacomini, E; Scotti, M.G; Lazarevic, D; Bartiromo, L; Schimberni, M; Alteri, A; Minetto, S; Morelli, M; Tonon, G; Viganò, P; et al.
Abstract: Study question: What is the transcriptomic response of decidualized endometrial stromal cells (DESCs) to the uptake of extracellular vesicles (EVs) secreted by human embryos? Summary answer: Human embryo derived EVs can impact DESCs transcriptomic profile via a cargo that can induce a positive effect on the expression of some decidualization‐related genes. What is known already: The establishment of an appropriate embryo–endometrial communication is essential for the implantation process and a successful pregnancy. Embryo-released factors are able to elicit biological effects on the endometrium. Among these, EVs secreted by embryos carry molecules potentially able to modulate endometrial function and favour the implantation process. However, most results come from animal species as few studies were performed using EVs derived from human embryos, due to difficulty in sample collection or ethical reasons. Study design, size, duration: EVs were isolated from one pool of IVF media where embryos were cultured between day 3 and 5 of development (blastocyst). Initially, DESCs(n = 4) were treated with different concentrations of EVs at different time points and RNA-sequencing was performed to define optimal conditions.Subsequently, EVs were isolated from one pool of IVF media where blastocysts diagnosed as euploid were cultured (EVe). To increase the reliability of the results, DESCs(n = 5) were treated with EVe using the optimal conditions. Participants/materials, setting, methods: EVs were isolated by differential ultracentrifugation from spent media of in vitro cultured human blastocyst stage embryos and from an equal volume of control medium (not exposed to embryos). DESCs were in vitro decidualized (E2:10nM+ P4:1uM+cAMP:0.5mM) and treated with different concentrations of EVs (10µg, 50µg, 100µg) for 24hours and 48hours. RNA-sequencing analysis was then performed. Once established the conditions that allow to better detect differences in trascriptomic profile, RNA-sequencing analysis on DESCs treated specifically with EVe was performed. Main results and the role of chance: The best response of DESCs to EVs uptake was induced by treatment with 10µg of EVs for 48hours. Using this condition, differential gene expression analysis allowed the identification of 166 upregulated and 124 downregulated genes in DESCs treated with EVe, when compared to DESCs treated with control. Based on Over-Representation analysis, DESCs treated with EVe were found to be enriched in transcripts of genes involved in signalling and cell communication. Moreover, based on Gene Set Enrichment Analysis results, EVe may regulate decidualization and the implantation process by targeting cholesterol biosynthesis and metabolism pathways, being among the most enriched pathways. The depletion of transcripts related to inflammatory and IL1R pathways in DESCs treated with EVe was also observed, suggesting a role of EVe in the fine regulation of inflammatory/immunomodulatory events occurring during implantation. At the intersection of genes whose expression was modified by EVe-treatment and those modified by the decidualization treatment, thirty-one transcripts exhibited the same trend, demonstrating that EVe exerted a positive effect on decidualization‐related genes expression in DESCs. Specifically, expression of genes involved in the implantation process ( PTGER2, IL15, WNT4 ) increased after decidualization and were further up-regulated after EVe-treatment, confirming the crucial role of EVs in the embryo-endometrium cross-talk. Limitations, reasons for caution: Larger studies are needed to validate these findings. Wider implications of the findings: EVs derived from human euploid embryos can evoke a specific transcriptional response in DESCs. Moreover, we speculate that these EVs may exert favourable effects on the endometrial tissue, increasing its receptivity for embryo implantation by modulating decidualization-related genes expression. Trial registration number: not applicable